Role of Tissue Doppler Echocardiography in Assessment of Post Myocardial Infarction Ischemic Mitral Regurgitation - Hasan Salah Mohamed (African Journal of Advanced Pure and Applied Sciences, 2026)
Ischemic mitral regurgitation (IMR) represents a common sequela of myocardial infarction and arises primarily from adverse left ventricular (LV) remodeling rather than intrinsic mitral valve pathology. Alterations in LV geometry lead to papillary muscle displacement and leaflet tethering, resulting in functional regurgitation. Variations in tethering configuration, namely symmetric and asymmetric patterns, are thought to influence the mechanism and severity of chronic IMR. This study sought to investigate the relationship between IMR mechanisms, regurgitation severity, and mitral annular deformation using two-dimensional echocardiography and tissue Doppler imaging (TDI).Twenty-four patients with chronic post-infarction IMR were prospectively enrolled and classified according to tethering pattern into symmetric (n = 15) and asymmetric (n = 9) groups. Comprehensive transthoracic echocardiography was performed to assess LV remodeling, mitral valve deformation indices, and MR severity using quantitative Doppler techniques. Regional systolic and diastolic mitral annular velocities were evaluated at six annular sites using TDI.Symmetric tethering was consistently associated with centrally directed regurgitant jets, whereas asymmetric tethering demonstrated posteriorly directed jets. Although LV dimensions and ejection fraction were comparable between groups, patients with asymmetric IMR exhibited significantly larger effective regurgitant orifice area, regurgitant volume, and regurgitant fraction (p < 0.05). In contrast, symmetric IMR was characterized by significantly greater coaptation height, tenting area, and mitral annular area (p < 0.01). TDI analysis revealed more diffuse systolic dysfunction in symmetric IMR, while asymmetric IMR showed regionally confined abnormalities corresponding to infarcted myocardial segments.These findings indicate that IMR comprises distinct echocardiographic phenotypes determined by leaflet tethering pattern, each associated with specific ventricular remodeling characteristics, mitral valve deformation, and regurgitation severity. Mitral annular TDI provides incremental value in assessing regional and global LV function in this population.